The Integration of EdTech Apps for Language Teaching - Parra, Miguel A. (CIEX JOURNAL, 2024)
The rapid evolution of technologies shows us the importance of being aligned with them to be updated and be involved in the practical digital tools that technology offers us, where, in most cases, technology is used in every language class. Furthermore, teachers can implement classroom activities using educational technology apps as a complementary tool, which improves language learning. This workshop will explore how educational technology applications can enrich language teaching by allowing students to explore new ways of learning entertainingly through gamification, online assignments rich in multimedia, and live interactive tasks. These consequently attract their attention and improve their language performance in developing reading, listening, writing, and speaking skills.